Molecular size of interacting and degrading polysaccharides - Jumel, Kornelia (1994)
The use of multi angle laser light scattering on-line to size exclusion chromatography, analytical ultracentrifugation and viscosity measurements for the determination of molecular weights and conformations of polysaccharide systems is described. The use of several independent techniques for the characterization of polysaccharide systems was found to be essential due to the polydisperse nature of the materials. These techniques were used to investigate the changes in molecular size and conformation of guar gum due to irradiation. Molecular weights and viscosities were found to decrease significantly with increasing radiation dose. Conformational studies on the resulting series of homologous samples confirmed the random coil-like conformation of guar gum. Investigations on BSNdextran complexes, obtained by dry-heating at different molar ratios showed that complex formation (most likely by a Maillard-type reaction) only took place when a low molecular weight dextran fraction was used. The highest molecular weight complexes were obtained when the BSA ratio was high, suggesting that some form of association between individual complexes and/or BSA had taken place.